Conflict Detection in Language Processing: Using Affect Control Theory to Predict Neural Correlates of Affective Incongruency in Social Interactions - Gesche Schauenburg; Arash Aryani; Chun-Ting Hsu; Tobias Schröder; Markus Conrad; Christian von Scheve; Arthur M. Jacobs (KZfSS Kölner Zeitschrift für Soziologie und Sozialpsychologie, 2024)
Abstract Affect control theory (ACT) is a~sociological theory of meaning processing in social interactions. Meaning, according to ACT, derives from cultural institutions and situational affordances, having denotative (declarative) as well as connotative (affective) properties. Mathematical formalizations of ACT allow predictions of affective incongruency (in the terminology of ACT, deflection ), which arises from conflicting institutional and situational meanings in a~given interaction context. Although ACT is theoretically consistent, its propositions regarding cognitive and affective processing have rarely been tested. The present study fills this gap by investigating the neural processing of affective incongruency in linguistic descriptions of social interactions. Following a~neurosociological paradigm, the study draws on neurocognitive evidence on the effects of words' affective content on word processing as well as on a~previous electroencephalography study that investigated processing of affective incongruency using event-related brain potentials. We hypothesized that affective incongruency is associated with activation in the anterior cingulate cortex (ACC), a~brain area known for conflict processing. To test this hypothesis, we replicated the electroencephalography study using functional magnetic resonance imaging: We visually presented sentences describing social interactions to 23~participants in a~silent reading task while measuring differences in the hemodynamic response in two conditions of affective congruency. Results show expected increases in neural activity for affectively incongruent sentences in the left ACC, supporting the assumption that affective language content influences meaning-making at very early semantic processing stages. The results also add to the emerging neuroscientific evidence for ACT's mathematical model of impression formation. @Die Theorie der Affektsteuerung (Affect Control Theory) ist eine soziologische Theorie zur Verarbeitung von Bedeutung in der sozialen Interaktion. Bedeutung speist sich darin sowohl aus institutionalisierten als auch aus situativen Gegebenheiten und umfasst denotative (deklarative) wie konnotative (affektive) Dimensionen. Die mathematische Formalisierung der Theorie erlaubt Vorhersagen der affektiven Kongruenz oder Stimmigkeit (,,affective deflection“) einer Interaktionssituation, die sich aus dem Zusammenspiel institutionalisierter und situativer Bedeutungen ergibt. Obgleich theoretisch konsistent, sind die Thesen der Theorie zum Zusammenspiel kognitiver und affektiver Bestandteile von Bedeutung nur selten empirisch überprüft worden. Die vorliegende Studie schließt diese Lücke, indem sie die neuronale Verarbeitung affektiver Inkongruenz in der sprachlichen Darstellung sozialer Interaktionen untersucht. Einem neurosoziologischen Paradigma folgend, stützt sich die Studie auf neurokognitive Befunde zur Rolle der affektiven Konnotation von Wörtern in der visuellen Wortverarbeitung sowie eigene Befunde zur neurophysiologischen Verarbeitung affektiver Inkongruenz mittels ereigniskorrelierter Hirnpotenziale. Wir testen die Hypothese, dass die affektive Inkongruenz sozialer Interaktion mit der Aktivierung des anterioren cingulären Cortex (ACC) korreliert, einem Hirnareal, das an der Verarbeitung konfligierender Informationen beteiligt ist. Dazu replizieren wir ein bestehendes Experimentaldesign unter Nutzung funktioneller Magnetresonanztomographie (fMRT): Im Rahmen einer Leseaufgabe präsentieren wir 23~Teilnehmerinnen und Teilnehmern visuell Sätze, die soziale Interaktionen beschreiben, und messen Unterschiede in der hämodynamischen Reaktion unter zwei Bedingungen affektiver Inkongruenz. Die Ergebnisse zeigen die erwartete Zunahme der neuronalen Aktivität im linken ACC in der Bedingung hoher affektiver Inkongruenz. Dies stützt die Annahme, dass die affektive Konnotation von Begriffen die Genese von Bedeutung in sozialen Interaktionen bereits in frühen semantischen Verarbeitungsstufen bedingt. Die Befunde können zudem als neurowissenschaftliche Evidenz für die mathematische Formalisierung der Theorie der Affektsteuerung gelten.
Keywords: 330; Neurosociology; Sociology of emotion; Affective meaning; Situational meaning; fMRI; Symbolic interactionism; Neurosoziologie; Soziologie der Emotionen; Affektive Bedeutung; Situative Bedeutung; fMRT; Symbolischer Interaktionismus